India - Kusy, Frank (Cadogan guides, 1996)
This fourth edition of Frank Kusy's best-selling guide to India's most popular places and how to get to them has 30% more information on destinations throughout the continent, with special additions on the increasingly popular south including Goa. As well as those places you know you must see, there are trips to wonders off the tourist trail, and sections in wildlife parks and trekking. Plus the latest information on literally hundreds of places to eat and stay; on the best festivals, shops and markets; on what to buy where, and how to bargain.